The Information Gap in higher Education in South Africa - McLoughlin, Kevin James; Dwolatzky, Barry (South African Journal of Higher Education, 2016)
Raising employment and improving the quality of education, are the two most critical and interrelated challenges, for eliminating poverty and reducing inequality in South Africa. To improve the quality of education, role-players need seamless access to critical information to guide planning and determine progress in different parts of the education system. Shortcomings in the current information infrastructure, especially at the nexus of the basic education and higher education systems, result in an information gap that needs to be eliminated, before a comprehensive picture of the education system and the factors underpinning its performance, can emerge. Local and international experts were consulted to understand best practice, describe information requirements and uncover the shortcomings in the existing infrastructure. Participants from the majority of the country’s higher education institutions took part in a survey to verify and refine the shape and consequences of the information gap. This article provides a foundation for creating an improved infrastructure that would provide the missing, critical information, highlighted in this study.